Preparation and ocular pharmacokinetics of hyaluronan acid-modified mucoadhesive liposomes. (3rd May 2016) - Lin, Jing; Wu, Hongjie; Wang, Yingjun; Lin, Jianhong; Chen, Qing; Zhu, Xuan
Abstract: The aim of this research was to formulate a liposomal preparation of DOX to be applied topically, and to investigate the in vitro and in vivo performance of the prepared liposomes. DOX liposomes were prepared by the solvent evaporation method, and then modified with bioadhesive material HA. Through MTT assay, we found that the safe concentration of liposomes delivered would hit 1 mg/mL. Cellular uptake studies showed that DOX liposomes coated with HA are much more targetable to cell nucleus. Their ocular pharmacokinetics in rabbits were investigated through the comparison with those obtained after dosing with non-modified liposomes and DOX solution. The in vitro transcorneal permeability of DOX in both kinds of liposomes was found to be slower than that of the solution because of sustained release. After in vivo instillation in rabbits, HA-modified liposomes had the longest retention time, following with naked liposomes. Significantly, the area under the curve of the aqueous humor concentration–time profiles of DOX liposomes was found to be 1.7-fold higher than that of DOX solution. The confocal experiment confirmed that HA-modified liposomes were able to maintain a higher DOX concentration and residence time than that of non-modified liposomes and free DOX. These results suggest that our liposomal preparation was of great help to improve the bioavailability of DOX.